Genetic Predisposition to Cardiac Conduction Defects in a Multi-Ethnic Population: A Case-Control Study in Palembang, Indonesia - Hidayat, Rachmat (Sriwijaya Journal of Internal Medicine, 2023)
Introduction: Cardiac conduction defects (CCDs) represent a significant global health burden, contributing to morbidity and mortality. While environmental and lifestyle factors are recognized contributors, genetic predisposition plays a crucial role in their development. This study aimed to investigate the association between specific genetic variants and CCDs in the diverse multi-ethnic population of Palembang, Indonesia. Methods: A case-control study was conducted involving 200 cases with CCDs (atrioventricular block, bundle branch block, sick sinus syndrome) and 200 age- and sex-matched controls from Palembang, Indonesia. Participants underwent detailed clinical evaluations, electrocardiography, and genotyping for selected single nucleotide polymorphisms (SNPs) previously associated with CCDs. These SNPs were located in genes encoding ion channels (SCN5A, KCNQ1, KCNH2), connexin proteins (GJA1, GJA5), and transcription factors (NKX2-5, TBX5). Logistic regression analysis was performed to assess the association between SNPs and CCDs, adjusting for potential confounders such as age, sex, hypertension, diabetes mellitus, and smoking status. Results: Several SNPs showed significant associations with CCDs in the Palembang population. The SCN5A rs1805124 variant was associated with an increased risk of atrioventricular block (OR 1.85, 95% CI 1.12-3.05, p=0.016). The KCNQ1 rs1801252 polymorphism was linked to a higher risk of bundle branch block (OR 2.10, 95% CI 1.30-3.40, p=0.002). Additionally, the GJA5 rs10453535 variant was associated with an increased risk of sick sinus syndrome (OR 1.72, 95% CI 1.05-2.82, p=0.031). These associations remained significant after adjusting for potential confounders. Conclusion: This study provides evidence for the genetic predisposition to CCDs in the multi-ethnic population of Palembang, Indonesia. Specific SNPs in SCN5A, KCNQ1, and GJA5 genes were associated with increased risks of various CCDs. These findings contribute to our understanding of the genetic basis of CCDs and may have implications for risk stratification and personalized management strategies.